Islamic learning in Arabic-Afrikaans between Malay model and Ottoman reform - Versteegh, Kees (UI Scholars Hub, 2015)
Through the second half of the nineteenth and the first half of the twentieth century the Muslim community of Cape Town produced a large number of texts in various fields of Islamic learning, written in Afrikaans, a creolized variety of the language the Dutch traders had brought to South Africa. The Cape Muslim community had its origin in South Asia and Southeast Asia; most of its founding members had been transported by force by the Dutch colonial authorities. Malay was the language in which they had been educated, and for some time it remained in use as the written language. For oral instruction, the Cape Muslim community soon shifted to Afrikaans. At the end of the nineteenth century, the Ottoman scholar Abu Bakr Effendi introduced the use of Afrikaans in Arabic script, replacing Malay as written language. In this paper I deal with the shift from Malay to Afrikaans and the relationship between Malay heritage and Ottoman reform in the Cape community.